The prevention role of Spirulina platensis (Arthrospira platensis) on intestinal health - Ender Deniz Asmaz; Nilay Seyidoglu (Food Science and Human Wellness)
Spirulina is a popular herbal food that has a preventive effect on health. In the study, it aimed to evaluate the effects of different doses of Spirulina platensis (Arthrospira platensis) on the morphological properties of the duodenum of rats, and to assign the effect of Spirulina on the expression of proliferating cell nuclear antigen (PCNA) in the rat duodenum, and thereby to observe the effects on intestinal health. 30 male Wistar albino rats were divided into 3 groups for 45 days. The first group was received the basal diet; the second group was given 500 mg/kg Spirulina daily by oral gavage; the third group was given 1000 mg/kg Spirulina daily. The duodenum segments were taken at the end of the trial and processed for histological assay. Although the total mucosa, villus height and villus/cript ratio were found higher in high dose Spirulina, the lower cript depth was detected in same group compared to control and low dose group. A significant increase was observed at high dose compared to the control and low dose group in terms of PCNA expression intensity and proliferation index. Findings suggest that high dose of Spirulina may support the duodenal growth, and thereby intestinal health.